PENERAPAN MULTIMEDIA PEMBELAJARAN SEBAGAI STRATEGI PENINGKATAN MINAT BELAJAR MATEMATIKA KELAS XII SMAN 2 KOTA JAMBI - MAHYUNIS MAHYUNIS (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2022)
This study aims to apply learning multimedia as a strategy to increase interest in learning mathematics in class XII at SMA Negeri 2 Jambi City in the 2019/2020 school year. This research is classified as classroom action research (CAR) through 4 stages, namely planning, implementation, observation and reflection. The population in this study were all students of class XII and the subjects were 30 people who were taken by random sampling. Data collection techniques through the method of observation, field notes, and documentation. The results showed an increase in interest in learning by being given action in accordance with the 6 steps of learning mathematics using computer-based multimedia learning, namely: 1. Information presentation, 2. Questions and responses, 3. Response assessment, 4. Giving feedback, 5. Repetition, 6. Lesson setting segment. This is indicated by an increase in the percentage of each indicator of interest in learning mathematics, namely: student's preference for teaching material before action 39.33% after action increases to 76.67%, student interest in teaching material before action 45.33% after action increases to 72 %, students' attention during the lesson from before the action 32.67% after the action increased to 70.67%, student involvement in the learning process from before the action 40.67% after the action increased to 64%. Based on the description above, it can be concluded that the application of computer-based learning multimedia can increase students' interest in learning. ABSTRAKPenelitian ini bertujuan untuk menerapkan multimedia pembelajaran sebagai strategi dalam meningkatkan minat belajar matematika kelas XII di SMA Negeri 2 Kota Jambi tahun pelajaran 2019/2020. Penelitian ini termasuk jenis penelitian tindakan kelas (PTK) melalui 4 tahapan yaitu perencanaan, pelaksanaan, observasi dan refleksi. Populasi dalam penelitian ini adalah seluruh siswa kelas XII dan subjek berjumlah 30 orang yang diambil dengan teknik acak (random sampling). Teknik pengumpulan data melalui metode observasi, catatan lapangan, dan dokumentasi. Hasil penelitian menunjukkan peningkatan minat belajar dengan diberi tindakan sesuai dengan 6 langkah pembelajaran matematika menggunakan multmultimultimedia pembelajaran berbasis komputer yaitu: 1. Penyajian informasi, 2. Pertanyaan dan respons, 3. Penilaian respons, 4. Pemberian balikan respons, 5. Pengulangan, 6. Segmen pengaturan pelajaran. Hal ini ditunjukkan dengan adanya peningkatan presentase setiap indikator minat belajar matematika yakni: kesukaan siswa terhadap materi ajar sebelum tindakan 39,33% setelah tindakan meningkat menjadi 76,67%, ketertarikan siswa terhadap materi ajar sebelum tindakan 45,33% setelah tindakan meningkat menjadi 72%, perhatian siswa saat pelajaran dari sebelum tindakan 32,67% setelah tindakan meningkat menjadi 70,67%, keterlibatan siswa terhadap proses pembelajaran dari sebelum tindakan 40,67% setelah tindakan meningkat menjadi 64%. Berdasarkan uraian diatas dapat disimpulkan bahwa penerapan multimedia pembelajaran berbasis komputer dapat meningkatkan minat belajar siswa.